DIGITAL MEDIA AND FILM INDUCED TOURISM: PIONEERING NEW DESTINATIONS FOR THE WANDERLUSTS - Thampi, Aiswarya; Balakrishnan K (International Journal of Psychosocial Rehabilitation, 2020)
-Digital media as well as films act as information reserve and serve as platform for communication for tourists. This phenomenon has significantly grown over the years. Rather than easing mobility and interactivity, digital media have been a tool of contributory in making convergence a reality. The visuals speak louder than words, and they are powerful enough to move people. This paper examines how films and digital media play a key role in increasing destination desires and tourism growth. Various kinds of media are found to be helpful and persuading for travelers in choosing a destination to travel and to plan trips. In fact, travelers endeavor to seek out tourism data, with the help of digital media before, after and during their travel. Travelers often share their experiences, merits and demerits about the destination through media; travel vlogs, films, reality show etc.Providing reviews and visuals to audience helps in successfully extending the demand for a selected destination. Places which were not that important suddenly shoot into prominence and become attractive tourist destinations as they get depicted in films and digital media. Consequently, the area gets an economic boost through the development of hospitality industry, transportation, purchase centers and several kinds of employment in the service sector. There is thus a fruitful interface between film and digital media with tourism through a process of mutual impact. The paper analyses the topic from the perspective of push and pull theory of motivation.